Zmiany modelu zatrudnienia w przedsiębiorstwach - Bąk-Grabowska, Dominika (Changes in the Model of Employment within Companies, 2008)
The paper describes orientations of changes in the field of structures and forms of employment. They are presented in the light of an increasing flexibility and setting up virtual firms. These type of changes generate complex problems in the human resources area. It is a big challenge for managers in contemporary companies. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 34, s. 98-107